2018
DOI: 10.1007/s00267-018-1095-5
|View full text |Cite
|
Sign up to set email alerts
|

Digital Technologies for Forest Supply Chain Optimization: Existing Solutions and Future Trends

Abstract: The role of digital technologies for fostering sustainability and efficiency in forest-based supply chains is well acknowledged and motivated several studies in the scope of precision forestry. Sensor technologies can collect relevant data in forest-based supply chains, comprising all activities from within forests and the production of the woody raw material to its transformation into marketable forest-based products. Advanced planning systems can help to support decisions of the various entities in the suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 122 publications
0
62
0
2
Order By: Relevance
“…GIS is therefore frequently found in forestry curricula (see e.g. Scholz et al, 2018;Arevalo et al, 2010), but a didactical combination of AR and GI-Science tools and methods with forest inventory and mensuration techniques is not widely implemented in higher education curricula, although using virtual reality in technical training is becoming more and more popular (Cochrane, 2016), for example as instruction for operating chainsaws, in flight simulations or in medical school training. However, to the best of our knowledge, only a few studies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…GIS is therefore frequently found in forestry curricula (see e.g. Scholz et al, 2018;Arevalo et al, 2010), but a didactical combination of AR and GI-Science tools and methods with forest inventory and mensuration techniques is not widely implemented in higher education curricula, although using virtual reality in technical training is becoming more and more popular (Cochrane, 2016), for example as instruction for operating chainsaws, in flight simulations or in medical school training. However, to the best of our knowledge, only a few studies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile devices such as tablets and smartphones will play an increasing role in the future of data collection within the forest [67]. Scholz et al [5] have already revealed that there is a need for an integrated, near real-time, and process oriented solution combining sensor measurements, positioning and spatial data. In this article, we presented a role-tailored map dashboard prototype that aims at fulfilling all these requirements using the map metaphor and a responsive design.…”
Section: Discussionmentioning
confidence: 99%
“…Scholz et al [5] performed a literature review regarding the digitization of the FbSC and provide guidelines for the development of technologies to improve the information flow in FbSCs. The article concludes that higher sustainability and efficiency of the FbSC requires a seamless information flow between the entities present in the FbSC [6][7][8][9][10].…”
Section: Relevant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Flexible trucking systems require real-time information and communication technologies [5] for optimization [31,32]. It requires massive investment and the sharing of needs and/or resources based on collaboration among stakeholders [33] while it is rarely fixed in time [34]. The result of this study enables a company to choose alternatives to secure the throughput by independent management means such as outsourcing or preparing buffer storage according to the estimated production loss as risk hedging [35].…”
Section: Discussionmentioning
confidence: 99%